Psoriasis in childhood and adolescence - Seyhan, Muammer; Coskun, Basak Kandi; Saglam, Hulya; Ozcan, Hamdi; Karincaoglu, Yelda (Wiley, 2006)
Background: The present study was aimed to define the gender ratio, familial occurrence, age of onset, precipitating factors, clinical types, nail and joint involvement of psoriasis in childhood and adolescence in Turkey. Methods: A total of 61 children with psoriasis under 18 years old were evaluated retrospectively, for age, gender, age of disease onset, family history, concomitant disease, the clinical type of psoriasis, clinical localization, nail and joint involvement and treatment modalities. Results: Of the patients, 23 (37.70%) were boys and 38 (62.30%) were girls. Mean age was 9.28 +/- 4.02 years in girls and 11.18 +/- 3.85 years in boys (9.96 +/- 4.03 years in all children). Mean age at the onset of the disease was 6.81 +/- 4.11 years in girls and 7.03 +/- 4.28 years in boys (6.89 +/- 4.14 years in all patients). In 14 (23%) cases, a positive family history was detected. The most frequent probable triggering factors were upper respiratory tract infections (14.8%) and positive throat culture for A group ss-hemolytic streptococcus (21.3%). Frequency of emotional stress and psychiatric morbidity were 54% and 9.8%, respectively. The most frequent localizations at onset were trunk (44.3%), extremities (54.0%), and scalp (36.0%). Three children (4.9%) had a history of dissemination from psoriatic diaper rash. In total, 51 (83.6%) patients presented with psoriasis vulgaris, eight (13.1%) with generalized pustular psoriasis, and the remaining two (3.3%) with erythrodermic psoriasis. Conclusions: The incidence of psoriasis among dermatological patients in childhood and adolescence was 3.8%. The disease tends to appear earlier in girls than boys. The authors suggested that stress and upper respiratory infections are the most important triggering factors in childhood and adolescence psoriasis.
Keywords: adolescence; childhood; psoriasis